(untitled) (Acta Entomologica Serbica, 2016)
New data on the distribution of singing cicadas in Serbia were collected with a bioacoustic approach. Six species were detected in SW Serbia and on Mt. Avala between 4 and 12 June, 2014. Three of the species are new for this country − Cicadetta montana sensu stricto, C. cantilatrix and C. macedonica. For the other three species, Dimissalna dimissa, Cicadivetta tibialis and Tettigettula pygmea, new distributional data are reported.